Using Experimental and Neurological Data to Gain a Deeper Understanding of Realization Utility Theory - Gibson, Scott; Seiler, Michael J.; Walden, Eric (Real estate economics, 2019)
Starting with the premise that realization utility theory helps explain trading behavior, this study combines a carefully crafted experimental design with functional magnetic resonance imaging technology to offer a more inclusive examination of factors that affect REIT trading behavior beyond whether a REIT is simply trading up or down. We add to the nascent field of neurological real estate by finding that local gains/loss domains are more relevant than are global gain/loss considerations, financial skewness is a significant determinant of trading behavior, and that performance inside the REIT market influences how hard subjects think when performing tasks outside the market.